PENGARUH DISIPLIN KERJA DAN BEBAN KERJA TERHADAP KINERJA GURU PADA SEKOLAH XYZ - Dhea Silvia Putri; Hasanuddin Hasanuddin; Jumawan Jumawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the Influence of Work Discipline and Workload on Teacher Performance at XYZ School. The research method used in this study is a quantitative method. The sampling technique in this study used a saturated sample or census of 42 teachers as respondents. The data collection technique used a questionnaire in several questions and was measured using a Likert Scale. Data analysis used the Structural Equation Modeling (SEM) method. Data was processed using SMART PLS 4.1 software. The results showed that (X1) Work Discipline had a positive and significant effect on teacher performance. In addition, (X2) Workload had a positive and significant effect on teacher performance.